Rekomendasi Sistem ERP untuk Akurasi Data Operasional Studi Kasus Stock dan Inventory CV ABC - Negara, Axel Shira Sapata; Enhartana , Afganta Chezar; Saputra, Zainudin; Aji, Rizal Fathoni (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
CV ABC is an SME in the retail sector that specializes in the sale of specialty goods and hobby supplies. The company currently relies on manual methods for sales recording and inventory management. The risk of inaccuracies in stock, inventory, and sales data leads to operational inefficiencies and the risk of losing customers. This study aims to provide the most suitable ERP recommendations for CV ABC to improve operational efficiency and the accuracy of stock and inventory data. Business process modeling was conducted using BPMN visualization to represent CV ABC’s current business processes with manual inventory management (as-is) and the recommended business processes upon ERP implementation that support efficient inventory management (to-be). Open-source ERP is considered the most suitable for implementation in SMEs in general and CV ABC in particular. The methodology used includes data collection through interviews and observations, BPMN modeling for visualizing as-is and to-be business processes, and the selection of open-source ERP systems using the AHP approach. Based on the AHP analysis, Odoo was determined to be the open-source ERP system best suited to CV ABC’s business needs and preferences compared to Dolibarr and Tryton. Odoo excels in the criteria of vendor reputation, ease of use, information requirements, and integration.